Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation Report on Self-Evaluation at the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) evaluation report on Self-Evaluation at the IMF. The implementation plan proposes specific actions to address the recommendations of the IEO that were endorsed by the Board in its September 18, 2015 discussion of the IEO's report, namely: (i) adopt a broad policy or general principles for self-evaluation in the IMF, including its goals, scope, outputs, utilization, and follow-up; (ii) give country authorities the opportunity to express their views on program design and results, and IMF performance; (iii) for each policy and thematic review, explicitly set out a plan for how the policies and operations it covers will be self-evaluated; (iv) develop products and activities aimed at distilling and disseminating evaluative findings and lessons. The implementation of some of these proposed actions is already underway. The paper also explains how implementation will be monitored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet